A Pilot Study on the Freelisting Method Among Adolescents with Chronic Musculoskeletal Pain: Feasibility, Acceptability and Study Findings - Sabrina Gmuca; Dori Abel; Mackenzie McGill; Daneka Stryker; Eda Akpek; Whitney Eriksen; Pamela F. Weiss; Peter F. Cronholm (Children)
Background/Objectives: To assess the feasibility and acceptability of freelisting for adolescents with chronic musculoskeletal pain (CMP) and use freelisting to identify how adolescents with CMP cope with pain. Methods: This was a mixed-methods cross-sectional single-center study of patients 12–18 years old, diagnosed with CMP. Twenty-seven subjects participated in an interview which included the freelisting exercise, probing questions, Connor-Davidson Resilience Scale 10-item, and semi-structured interview. Feasibility was pre-defined as ≥85% completion. A list of ‘standardized’ freelisting terms was created, and we calculated Smith’s salience index. Freelisting terms were grouped into individual, family, friends, school, and medical domains. Results: In this predominantly female population, resilience levels were low to moderate, and on average, participants had moderate pain intensity and functional disability. The freelisting exercise was feasible and acceptable among females, with low recruitment of males. Salient words to describe adolescents’ pain included frustrating, upsetting, annoying, and painful. Participants identified family, friends, teachers, guidance counselors, and health professionals as key sources of support. Many participants reported difficulties communicating their pain. Helpful coping strategies included rest, distraction, relaxation, endurance, and extracurricular participation. Conclusions: Freelisting was well perceived among female adolescents with CMP. Supportive relationships with community members play an important role for this population. However, perceived stigma may deter female adolescents from talking about their pain. Purposive sampling of male participants and recruitment strategies ensuring diverse patient representation are necessary to ensure generalizability of future results when using the freelisting method for adolescents with CMP.